Predicting the relationship between green transformational leadership, green human resource management practices, and employees' green behavior - Afriyadi Cahyadi; Diah Natalisa; József Poór; Badia Perizade; Katalin Szabó (Administrative Sciences, 2023)
Building on theories of Corporate Sustainability, Triple Bottom Line, and Natural Resource-Based View, this study aims to predict the positive relationship between green transformational leadership, green human resource management practices, and employees' green behavior. It applies a quantitative approach to analyze 252 data collected from the customers who are prospective employees of small and medium enterprises in Budapest. An online questionnaire was sent to 252 samples with the Snowball sampling method for about a month in Hungary. Based on a structural equation modeling analysis, green transformational leadership and green human resource management practices positively influence employees' green behavior. Green human resource management practices mediate the relationship between green transformational leadership and employees' green behavior. Small and medium enterprises should consider solving the green behavioral problems of their employees by promoting the green concept in leadership and human resource management practices. Such initiatives contribute to sustainability in small and medium enterprises.
Keywords: 350; corporate sustainability; employees' green behavior; green human resource management practices; green transformational leadership; natural resource-based view; small and medium enterprises; triple bottom line